Perovskite device and preparation method and application thereof
By using fluoropolymer materials with a double-layer encapsulation structure in perovskite devices, the decomposition problem of perovskite solar cells in high-temperature and oxygen environments has been solved, achieving long-term stability and repairability of the devices. This technology is applicable to fields such as photovoltaic cells, light-emitting diodes, photodetectors, memristors, and lasers.
Patent Information
- Application Number
- CN202411238179.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-01-14
AI Technical Summary
Existing perovskite solar cell encapsulation technology requires high temperatures and vacuum, which leads to the decomposition of perovskite materials, affecting device performance. Furthermore, the release of small molecules from the aging hot melt adhesive can damage functional materials, making it impossible to operate stably for a long time.
Fluoropolymers such as polytetrafluoroethylene, polydichlorofluoroethylene, and polydifluoroethylene are used as encapsulation layers and electronic buffer layers to form a double-layer encapsulation structure, which isolates water and oxygen and improves the stability of the perovskite layer.
It effectively resists water and oxygen erosion, prevents the decomposition of the perovskite layer, improves the long-term stability and repairability of perovskite devices, is suitable for industrial use, and meets the application requirements of photovoltaic cells, light-emitting diodes, photodetectors, memristors or lasers.
Smart Images

Figure HDA0005028368250000011 
Figure HDA0005028368250000012 
Figure HDA0005028368250000021
Abstract
Description
Technical Field
[0001] The present invention relates to the field of photovoltaic technology, and in particular to a perovskite device and a preparation method and application thereof. Background Art
[0002] Perovskite materials have excellent photoelectric properties such as long carrier diffusion length, adjustable optical band gap, high molar extinction coefficient and bipolar transmission. The perovskite battery devices prepared by them have the characteristics of solution preparation, simple manufacturing process, wide source of raw materials and high photoelectric conversion efficiency, which creates conditions for large-scale production and also makes perovskite optoelectronic devices widely used in solar cells and other fields.
[0003] Perovskite materials exposed to water and oxygen in long-term working conditions are prone to room temperature phase change, ion migration, phase segregation and other behaviors; and perovskite solar cells are also susceptible to extreme conditions such as high temperature, high humidity, oxygen, corrosive chemicals and external impact in the environment during operation, resulting in device damage, performance degradation and even failure, and cannot work stably in the natural environment for a long time. In order to ensure that the battery can work efficiently and stably for a long time, the battery cells must be encapsulated to isolate moisture and oxygen and improve the stability of perovskite solar cells. However, the existing perovskite solar cell encapsulation technology generally requires high temperature and vacuum operation, which will accelerate the decomposition of perovskite materials and thus affect the performance of perovskite solar cells; and after aging, polar small molecules are released from hot melt adhesives, which will have a destructive effect on perovskite functional materials. Summary of the invention
[0004] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, one of the purposes of the present invention is to provide a perovskite device; the second purpose of the present invention is to provide a method for preparing the perovskite device; the third purpose of the present invention is to provide an application of the perovskite device.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] A first aspect of the present invention provides a perovskite device, comprising an encapsulation layer, an electron buffer layer, a perovskite layer and an electron transport layer;
[0007] The encapsulation layer is disposed on the outer surface of the perovskite device;
[0008] The electron buffer layer is located between the perovskite layer and the electron transport layer.
[0009] Preferably, the materials of the encapsulation layer and the electronic buffer layer are independently selected from fluorine-containing polymers; further preferably, the fluorine-containing polymer includes at least one of polytetrafluoroethylene, polydifluoroethylene chloride, and polyvinyl difluoride.
[0010] Preferably, the fluorine-containing polymer materials such as polytetrafluoroethylene, polyvinyl difluoride and polyvinyl difluoride of the encapsulation layer have a low degree of polymerization; the fluorine-containing polymer materials such as polytetrafluoroethylene, polyvinyl difluoride and polyvinyl difluoride of the electronic buffer layer can have any degree of polymerization.
[0011] Specifically, fluorine-containing polymer materials such as polytetrafluoroethylene, polydifluoroethylene and polyvinyl difluoride have smaller atomic distances and very strong chemical bond forces. Among them, polytetrafluoroethylene is a high molecular polymer obtained by polymerization of tetrafluoroethylene as a monomer, with a chemical formula of (C2F4)n. It has excellent heat resistance and cold resistance and can be used for a long time at -180 to 260°C. This material is resistant to acids and alkalis, and to various organic solvents, and is almost insoluble in all solvents. At the same time, polytetrafluoroethylene has the characteristics of high temperature resistance, and the outer fluorine atoms have very strong hydrophobicity, so that it can form a stable packaging material, which plays a role in maintaining the stability of the perovskite structure.
[0012] Preferably, the thickness of the encapsulation layer is 80-10000 nm.
[0013] Preferably, the thickness of the electron buffer layer is 1-5 nm.
[0014] Preferably, the thickness of the perovskite layer is 20-1000 nm.
[0015] Preferably, the material of the perovskite layer has an ABX3 structure; wherein A includes at least one of methylamine, formamidine, and cesium; B includes at least one of Pb and Sn; and X includes at least one of I, Br, Cl, IBr, and ICl.
[0016] Preferably, the material of the perovskite layer includes at least one of MAPbBr3, FAPbI3, and CsPbI3.
[0017] Preferably, the electron transport layer comprises a first electron transport layer and a second electron transport layer which are connected.
[0018] Preferably, the material of the first electron transport layer includes C 60 、PC 61 BM, PC 71 At least one of BM.
[0019] Preferably, the material of the second electron transport layer includes at least one of BCP, SnO2, ZnO and TiO2.
[0020] Preferably, the thickness of the first electron transport layer is 10-100 nm.
[0021] Preferably, the second electron transport layer has a thickness of 2 to 100 nm.
[0022] Preferably, the perovskite device further comprises a conductive substrate, and the conductive substrate is located inside the perovskite device.
[0023] Preferably, the perovskite device further comprises a hole transport layer, and the material of the hole transport layer comprises at least one of PTAA, Spiro-OMeTAD and its derivatives, PACz and its derivatives, TAPC, NiO, and MPA-CPA.
[0024] Preferably, the perovskite device further comprises a metal electrode layer, and a material of the metal electrode layer comprises at least one of Cu, Ag, Al, Cr and Au.
[0025] Preferably, the hole transport layer has a thickness of 1 to 200 nm.
[0026] Preferably, the thickness of the metal electrode layer is 80-200 nm.
[0027] Preferably, the conductive base comprises a substrate and a conductive substance deposited on the substrate; the conductive substance serves as an electrode material.
[0028] Preferably, the substrate includes one of silicon on insulator (SOI) material, silicon wafer, silicon carbide, mica, glass, quartz sheet, copper foil, and polymer substrate; further preferably, the polymer substrate includes at least one of polyethylene, polymethyl methacrylate, polycarbonate, polyurethane, polyimide, chloroacetic acid resin, and polyacrylic acid.
[0029] Preferably, the conductive material includes at least one of indium tin oxide (ITO), fluorine-doped tin oxide (FTO), aluminum-doped zinc oxide (AZO), graphene, and carbon nanotube.
[0030] Preferably, the conductive substrate comprises one of FTO glass, ITO glass and AZO glass.
[0031] Preferably, the thickness of the conductive substrate is 0.8-1.5 mm; further preferably, the thickness of the conductive substrate is 0.8-1.3 mm.
[0032] Preferably, the thickness of the film layer of the conductive substance in the conductive substrate is 80 to 200 nm; further preferably, the thickness of the film layer of the conductive substance in the conductive substrate is 80 to 150 nm.
[0033] Preferably, the perovskite device is a formal structure or a trans structure; wherein the formal structure includes a conductive substrate, a second electron transport layer, a first electron transport layer, an electron buffer layer, a perovskite layer, a hole transport layer, a metal electrode layer and an encapsulation layer stacked in sequence from bottom to top; the trans structure includes a conductive substrate, a hole transport layer, a perovskite layer, an electron buffer layer, a first electron transport layer, a second electron transport layer, a metal electrode layer and an encapsulation layer stacked in sequence from bottom to top.
[0034] The second aspect of the present invention provides a method for preparing the perovskite device according to the first aspect of the present invention, comprising the following steps:
[0035] The electron buffer layer, the perovskite layer, the first electron transport layer, the second electron transport layer, the metal electrode layer and the hole transport layer are respectively deposited on the conductive substrate, and then the encapsulation layer is deposited on the outer surface to obtain the perovskite device.
[0036] Preferably, the hole transport layer and the perovskite layer are deposited by solution spin coating, respectively; the electron buffer layer, the first electron transport layer, the second electron transport layer, the metal electrode layer and the encapsulation layer are deposited by evaporation, respectively.
[0037] Preferably, the solution is spin-coated at a rotation speed of 2000 to 8000 rpm; further preferably, the solution is spin-coated at a rotation speed of 3000 to 5500 rpm.
[0038] Preferably, the vacuum degree of the evaporation is 1×10 -6 ~1×10 -5 Pa; further preferably, the vacuum degree of the evaporation is 1×10 -6 ~5×10 -6 Pa.
[0039] Preferably, the evaporation rate of the evaporation is 0.01-1.5 nm / s; further preferably, the evaporation rate of the evaporation is 0.1-0.3 nm / s.
[0040] Preferably, the conductive substrate is cleaned and surface treated before use; further preferably, the surface treatment includes at least one of ultraviolet ozone cleaning treatment, oxygen plasma treatment, and surface etching treatment.
[0041] Preferably, the specific operation of depositing the perovskite layer is: preparing a perovskite precursor solution, mixing the perovskite precursor solution at 20 to 80° C. for 10 to 1200 minutes, and then depositing the solution by solution spin coating.
[0042] Preferably, the perovskite precursor solution comprises the following preparation raw materials: an organic amine salt, an alkali metal halide, a divalent metal halide, a solvent, an additive and an anti-solvent.
[0043] Preferably, the organic amine salt comprises at least one of formamidine hydrochloride, methylamine hydrochloride (MACl), dimethylamine hydrochloride, formamidine hydrobromide, methylamine hydrobromide (MABr), dimethylamine hydrobromide, formamidine hydroiodide (FAI), methylamine hydroiodide, and dimethylamine hydroiodide.
[0044] Preferably, the alkali metal halide includes at least one of CsI, RbI, KI, NaI, LiI, CsBr, RbBr, KBr, NaBr, LiBr, CsCl, RbCl, KCl, NaCl, and LiCl.
[0045] Preferably, the divalent metal halide includes at least one of PbI2, PbBr2, PbCl2, GeI2, GeBr2, GeCl2, SnI2, SnBr2, and SnCl2.
[0046] Preferably, the solvent includes at least one of dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), and N-methylpyrrolidone (NMP).
[0047] Preferably, the additive includes at least one of hydrochloric acid, hydrobromic acid, hydroiodic acid, methylammonium chloride, methylammonium bromide, polyvinyl pyrrolidone, and polyethylene oxide.
[0048] Preferably, the concentration of the additive is 0.5-2 mg / mL.
[0049] Preferably, the anti-solvent comprises at least one of chlorobenzene, isopropanol, ethyl acetate and diethyl ether.
[0050] Preferably, the method for preparing the inverse structure perovskite device comprises the following steps:
[0051] (1) cleaning the conductive substrate and performing surface treatment on the substrate;
[0052] (2) depositing a hole transport layer onto the surface of the surface-treated conductive substrate by solution spin coating;
[0053] (3) depositing a perovskite layer on the surface of the hole transport layer by solution spin coating;
[0054] (4) depositing an electron buffer layer, a first electron transport layer, a second electron transport layer and a metal electrode layer in sequence on the perovskite layer by an evaporation method;
[0055] (5) Depositing the encapsulation layer on the surface of the perovskite device by evaporation to obtain the perovskite device.
[0056] The third aspect of the present invention provides the use of the perovskite device described in the first aspect of the present invention in a photovoltaic cell, a light emitting diode, a photodetector, a memristor or a laser.
[0057] Compared with the prior art, the present invention has the following beneficial effects:
[0058] 1) The perovskite device provided by the present invention has a double-layer packaging structure of an encapsulation layer and an electronic buffer layer, which can effectively resist the erosion of water and oxygen, prevent the decomposition of the perovskite layer, and improve the long-term stability and repairability of the perovskite device.
[0059] 2) The preparation method of the perovskite device provided by the present invention is simple, the material source is abundant, and it is suitable for industrial application.
[0060] 3) The perovskite device provided by the present invention has good storage stability and can meet the application requirements in the fields of photovoltaic cells, light-emitting diodes, photodetectors, memristors or lasers. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 Schematic diagram of the structure of the inverted perovskite device;
[0062] Figure 2 is a SEM image of the perovskite layer (a) and the electronic buffer layer (b) in Example 1;
[0063] Figure 3 is the absorption spectrum of perovskite film;
[0064] Figure 4 The contact angle test results of perovskite film;
[0065] Figure 5 The results of the air stability test of the perovskite film are shown in Figure 2.
[0066] Figure 6 is the XRD pattern of perovskite film;
[0067] Figure 7 is the steady-state spectrum of the perovskite film;
[0068] Figure 8 This is the transient spectrum of the perovskite film;
[0069] Fig. 9 This is the secondary ion mass spectrum of the perovskite device;
[0070] Fig.10 The photovoltaic performance test results of perovskite devices;
[0071] Fig.11 The storage stability test results of perovskite devices. DETAILED DESCRIPTION
[0072] The present invention is further described in detail below by specific examples. Unless otherwise specified, the raw materials, reagents or devices used in the examples and comparative examples can be obtained from conventional commercial sources or can be obtained by prior art methods. Unless otherwise specified, the experiments or test methods are conventional methods in the art.
[0073] Example 1
[0074] This embodiment provides a double-encapsulated perovskite device having a trans-structure. Figure 1 is a schematic diagram of the structure of the inverse perovskite device. Figure 1 It can be seen that the structure of the perovskite device is a conductive substrate, a hole transport layer, a perovskite layer, an electron buffer layer, a first electron transport layer, a second electron transport layer, a metal electrode layer and an encapsulation layer stacked in sequence from bottom to top.
[0075] Among them, the conductive substrate is 1.1mm thick ITO conductive glass, in which the ITO film thickness is about 100nm. Before use, it is ultrasonically cleaned with deionized water, acetone, ethanol and isopropanol for 10 minutes, blown dry with nitrogen, and then surface treated with ultraviolet light / ozone for 10 minutes to obtain a transparent conductive substrate and transferred to a glove box.
[0076] The material of the hole transport layer is MeO-2PACz. A layer of MeO-2PACz hole transport layer is spin-coated on the transparent substrate electrode, annealed at 100°C for 10 minutes, cooled, cleaned with ethanol, and spin-coated to obtain a single layer of hole transport layer with a thickness of about 1 nm.
[0077] Prepared with 1 mL DMF / DMSO (v / v=4:1) mixed solvent, 645.34 mg PbI2, 188.80 mg FAI, 0.75 mg MACl2, 8 mg MABr, 26.41 mg PbBr2, and 1 mg PEACl additive (MAPbBr3) 0.05 (FAPbI3) 0.95 The perovskite layer precursor solution was stirred at room temperature for 2 hours and then deposited on the hole transport layer by solution spin coating. The first step of the spin coating speed was 1000 rpm, the spin coating time was 10 s, the second step was 4000 rpm, the spin coating time was 30 s, and the acceleration was 2000 rpm / s. 100 μL of anti-solvent chlorobenzene solvent was added 10 s before the end of the second spin coating step to optimize the crystallization rate, followed by annealing at 100 ° C for 10 min. After the annealing was completed, a perovskite layer of about 600 nm thick was obtained. The perovskite layer was cooled to room temperature for use.
[0078] The cooled device is then placed in a vacuum deposition chamber and the vacuum is maintained at 10 -4Pa, a 2 nm thick polytetrafluoroethylene was deposited on the surface of the perovskite layer by evaporation as an electron buffer layer at a rate of Evaporate C on the surface of the electronic buffer layer 60 , the rate is Form a first electron transport layer with a thickness of 30 nm; evaporate BCP at a rate of A second electron transport layer with a thickness of 4 nm is formed. Copper is evaporated on the surface of the second electron transport layer at a rate of A metal electrode layer with a thickness of 100 nm was formed.
[0079] A 500nm thick polytetrafluoroethylene layer is evaporated on the entire device surface to form an encapsulation layer, thereby obtaining a double-encapsulated perovskite device.
[0080] Comparative Example 1
[0081] This comparative example provides a perovskite device, which differs from Example 1 only in that no electron buffer layer is provided. The structure of the perovskite device is a conductive substrate, a hole transport layer, a perovskite layer, a first electron transport layer, a second electron transport layer, a metal electrode layer and an encapsulation layer stacked in sequence from bottom to top, and the remaining structures and preparation methods are the same as those of Example 1.
[0082] Comparative Example 2
[0083] This comparative example provides a perovskite device, which differs from Example 1 only in that no encapsulation layer is provided. The structure of the perovskite device is a conductive substrate, a hole transport layer, a perovskite layer, an electron buffer layer, a first electron transport layer, a second electron transport layer and a metal electrode layer stacked in sequence from bottom to top, and the rest of the structure and preparation method are the same as those of Example 1.
[0084] Comparative Example 3
[0085] This comparative example provides a perovskite device, which differs from Example 1 only in that an electron buffer layer and an encapsulation layer are not provided. The structure of the perovskite device is a conductive substrate, a hole transport layer, a perovskite layer, a first electron transport layer, a second electron transport layer and a metal electrode layer stacked in sequence from bottom to top, and the rest of the structure and preparation method are the same as those of Example 1.
[0086] Performance Testing
[0087] 1. Scanning electron microscope test of the perovskite layer and the electronic buffer layer in Example 1:
[0088] In Example 1, after the perovskite layer and the electronic buffer layer were deposited, scanning electron microscope tests were performed respectively. Figure 2 is a SEM image of the perovskite layer (a) and the electronic buffer layer (b) in Example 1. Figure 2 It can be seen that the perovskite layer ( Figure 2(a)) and the electronic buffer layer ( Figure 2 There is no difference in the SEM images of (b)). The polytetrafluoroethylene electronic buffer layer is tightly spread on the upper interface of the perovskite layer, realizing the internal encapsulation of the perovskite layer.
[0089] 2. Absorption spectrum test of perovskite film:
[0090] The same perovskite layer precursor solution as in Example 1 was prepared and spin-coated on the surface of quartz glass to form a perovskite layer, and then a layer of polytetrafluoroethylene was deposited on the surface as an encapsulation layer to form a perovskite film covered with polytetrafluoroethylene. The perovskite film not covered with polytetrafluoroethylene was used as a control group, and the absorption spectra of the perovskite film covered with polytetrafluoroethylene and the perovskite film not covered with polytetrafluoroethylene were tested. Then, the absorption spectra of the two were tested again after aging on a hot stage at 65°C for 8 days in air with a relative humidity of 35%.
[0091] Figure 3 is the absorption spectrum of the perovskite film. Figure 3 It can be seen that the absorption spectrum curves of the perovskite film covered with polytetrafluoroethylene and the perovskite film not covered with polytetrafluoroethylene before aging coincide, indicating that covering the surface of the perovskite film with a polytetrafluoroethylene layer will not affect its light absorption characteristics; after aging for 8 days at 35% humidity and 65°C, the absorption spectrum curve of the perovskite film covered with polytetrafluoroethylene is basically consistent with that before aging, while the perovskite film not covered with polytetrafluoroethylene has deteriorated and has no effective absorption spectrum, indicating that covering the surface of the perovskite film with a polytetrafluoroethylene layer can effectively isolate water and oxygen and maintain good sunlight absorption characteristics.
[0092] 3. Contact angle and air stability test of perovskite film:
[0093] The same perovskite layer precursor solution as in Example 1 was prepared and spin-coated on a quartz glass surface to form a perovskite layer, and then a layer of polytetrafluoroethylene was deposited on the surface as an encapsulation layer to form a perovskite film covered with polytetrafluoroethylene. The perovskite film not covered with polytetrafluoroethylene was used as a control group, and the contact angles of the perovskite film covered with polytetrafluoroethylene and the perovskite film not covered with polytetrafluoroethylene were tested, and the film was aged at 35% humidity and 65°C for 12 days to conduct an air stability test.
[0094] Figure 4 is the contact angle test result of perovskite film, where: Figure 4 (a) is the perovskite film without polytetrafluoroethylene coating. Figure 4 (b) is a perovskite film covered with polytetrafluoroethylene. Figure 4 It can be seen that when the upper surface of the perovskite layer is encapsulated with polytetrafluoroethylene, the contact angle of water changes from 49.6° ( Figure 4 (a)) increased to 94.8°( Figure 4 (b) shows that when the upper surface of the perovskite layer is covered with polytetrafluoroethylene, the hydrophobicity of the perovskite layer is greatly improved, which can effectively prevent moisture from entering the perovskite layer and causing damage to the perovskite layer.
[0095] Figure 5 The results of the air stability test of the perovskite film are shown in Figure 2. Figure 5 (a) is the perovskite film without polytetrafluoroethylene coating. Figure 5 (b) is a perovskite film covered with polytetrafluoroethylene. Figure 5 It can be seen that the perovskite film without polytetrafluoroethylene ( Figure 5 (a)) began to decompose on the 4th day and completely deteriorated on the 7th day; while the perovskite film covered with polytetrafluoroethylene ( Figure 5 (b) After 12 days of aging, the film is almost the same as the initial state. Only the perovskite part on the edge that is not evaporated by polytetrafluoroethylene decomposes into yellow, indicating that polytetrafluoroethylene has a good protective effect on the perovskite film, and the perovskite film covered with polytetrafluoroethylene has good air stability.
[0096] 4. X-ray diffraction analysis, steady-state spectrum test and transient spectrum test of perovskite film:
[0097] The same perovskite layer precursor solution as in Example 1 was prepared and spin-coated on the surface of quartz glass to form a perovskite layer, and then a layer of polytetrafluoroethylene was deposited on the surface as an encapsulation layer to form a perovskite film covered with polytetrafluoroethylene, and a perovskite film not covered with polytetrafluoroethylene was used as a control group. X-ray diffraction analysis was performed on both at the initial stage, and at 35% humidity and 65°C for 3d, 5d and 8d of aging; steady-state spectrum test and transient spectrum test were performed at the initial stage, and after aging for 7d at 35% humidity and 65°C.
[0098] Figure 6 is the XRD pattern of the perovskite film, where Figure 6 (a) is the perovskite film without polytetrafluoroethylene coating. Figure 6 (b) is a perovskite film covered with polytetrafluoroethylene. Figure 6 (a) It can be seen that the XRD signal peak of the perovskite film not covered with polytetrafluoroethylene is very weak at the 5th day and completely disappears at the 8th day; Figure 6 (b) It can be seen that after covering with polytetrafluoroethylene, the XRD signal of the perovskite film remains unchanged on the 8th day.
[0099] Figure 7 is the steady-state spectrum of the perovskite film, where Figure 7 (a) is the initial steady-state spectrum. Figure 7 (b) is the steady-state spectrum after aging for 7 days. Figure 7It can be seen that after aging for 7 days, the spectrum of the perovskite film covered with polytetrafluoroethylene is normal, while the perovskite film not covered with polytetrafluoroethylene emits very weak light.
[0100] Figure 8 is the transient spectrum of the perovskite film, where Figure 8 (a) is the initial steady-state spectrum. Figure 8 (b) is the transient spectrum after aging for 7 days. Figure 8 It can be seen that Figure 8 It can be seen that after aging for 7 days, the transient fluorescence lifetime of the perovskite film not covered with polytetrafluoroethylene becomes very short, while the transient fluorescence lifetime of the perovskite film covered with polytetrafluoroethylene remains basically unchanged.
[0101] It can be seen that after covering the surface of the perovskite film with polytetrafluoroethylene, the stability of the perovskite film can be effectively improved, preventing moisture and other substances in the environment from damaging the perovskite.
[0102] 5. Secondary ion mass spectrometry test of perovskite devices:
[0103] The perovskite devices in Example 1 and Comparative Example 1 were subjected to secondary ion mass spectrometry tests, and the test time was initially and after the devices were placed in a nitrogen atmosphere for 30 days.
[0104] Fig. 9 is the secondary ion mass spectrum of the perovskite device, where Fig. 9 (a) is the secondary ion mass spectrum of the perovskite device in comparative example 1 at the initial stage, Fig. 9 (b) is the secondary ion mass spectrum of the perovskite device at the initial stage of Example 1, Fig. 9 (c) is the secondary ion mass spectrum of the perovskite device in comparative example 1 after being placed for 30 days. Fig. 9 (d) is the secondary ion mass spectrum of the perovskite device in Example 1 after being placed for 30 days. Fig. 9 (a) and Fig. 9 (c) It can be seen that in the sample after 30 days, the iodine ions of the perovskite were transferred to the electron transport layer, indicating that in the device encapsulated without the electron buffer layer, as time goes by, the ions in the perovskite will migrate into other functional layers, which not only accelerates the decay of the perovskite layer itself, but also destroys the role of other functional layers. Fig. 9 (b) and Fig. 9 (d) It can be seen that in the device encapsulated in the polytetrafluoroethylene electronic buffer layer in Example 1, the secondary ion mass spectrum of the device after 30 days is no different from that at the beginning, indicating that the polytetrafluoroethylene layer can effectively inhibit the ion migration in the perovskite layer, thereby inhibiting the decomposition of the perovskite layer, and improving the stability of the perovskite layer from the aspect of inhibiting element migration.
[0105] 6. Photovoltaic performance test of perovskite devices:
[0106] The photovoltaic performance of the perovskite devices in Example 1 and Comparative Example 1 was tested under a solar simulator with a light intensity of AM1.5G. Fig.10 The photovoltaic performance test results of perovskite devices are given by Fig.10 It can be seen that the open circuit voltage of the device in Example 1 is 1.19 V and the short circuit current density is 25.51 mA / cm 2 , the filling factor is 84.00%, and the photoelectric conversion efficiency is 25.49%. When the upper surface of the perovskite layer in the perovskite device is encapsulated with polytetrafluoroethylene, the interface defects are suppressed and the non-radiative recombination loss is reduced. The 2nm thick fluorine-rich encapsulation layer provides an electron channel, suppresses the passage of holes, reduces the energy loss of carriers and non-radiative recombination losses, and improves the device performance.
[0107] 7. Storage stability test of perovskite devices:
[0108] The long-term stability of the photoelectric performance of the perovskite devices in Example 1 and Comparative Examples 1-3 in air at 35% relative humidity and 25° C. was tested.
[0109] Fig.11 The storage stability test results of perovskite devices, where Fig.11 (a) is the storage stability test result of the perovskite devices in Comparative Examples 2 and 3, Fig.11 (b) is the storage stability test results of the perovskite devices in Example 1 and Comparative Example 1. Fig.11 (a) It can be seen that after the perovskite device in Comparative Example 2 was encapsulated in a polytetrafluoroethylene electron buffer layer, after aging for 672 hours, the energy conversion efficiency of the perovskite device was reduced to 95.7% of the original value. In Comparative Example 3, the perovskite device was not encapsulated in a polytetrafluoroethylene electron buffer layer, and the energy conversion efficiency of the perovskite device was reduced to 87.2% of the original value. In order to eliminate the attenuation effect of the electron transport layer, the electron transport layer and the metal electrode of the device aged for 672 hours were re-evaporated. After evaporation, the energy conversion efficiency of the perovskite device encapsulated in polytetrafluoroethylene in Comparative Example 2 was increased to 99.3% of the original value, while the energy conversion efficiency of the perovskite device in Comparative Example 3 that was not encapsulated in a polytetrafluoroethylene electron buffer layer was only increased to 92.5% of the original value. It can be seen that the polytetrafluoroethylene electronic buffer layer, as the inner encapsulation layer of the perovskite device, plays a good protective role for the perovskite layer, greatly improves the long-term stability of the perovskite device, and enables the perovskite device to have self-healing properties. Fig.11(b) It can be seen that the energy conversion efficiency of the perovskite device with a double-layer packaging structure in Example 1 after aging for 672 hours is 97.6% of the original energy conversion efficiency. The energy conversion efficiency of the perovskite device with only an external packaging structure in Comparative Example 1 after aging for 672 hours is 91.3% of the original energy conversion efficiency. It can be seen that the use of an internal and external double packaging structure is beneficial to improving the long-term stability of the perovskite device.
[0110] The perovskite device provided by the present invention adopts an internal and external double packaging structure, which significantly improves the storage stability of the device and reduces the defect state density of the device. By using fluorine-rich polymers such as polytetrafluoroethylene as the packaging layer material and utilizing the material's superior charge transport and ion migration inhibition properties, the long-term stability and other performance improvements of the perovskite material are achieved, so that it can meet the application requirements in the fields of photovoltaic cells, light-emitting diodes, photodetectors, memristors or lasers.
Claims
1. A perovskite device, characterized in that: It includes an encapsulation layer, an electron buffer layer, a perovskite layer and an electron transport layer; The encapsulation layer is disposed on the outer surface of the perovskite device; The electron buffer layer is located between the perovskite layer and the electron transport layer.
2. The perovskite device according to claim 1, characterized in that The materials of the encapsulation layer and the electronic buffer layer are independently selected from fluorine-containing polymers; Preferably, the fluorine-containing polymer includes at least one of polytetrafluoroethylene, polydichloroethylene difluoride and polyvinyl difluoride.
3. The perovskite device according to claim 1, characterized in that The thickness of the encapsulation layer is 80 to 10000 nm; And / or, the thickness of the electronic buffer layer is 1 to 5 nm; And / or, the thickness of the perovskite layer is 20 to 1000 nm.
4. The perovskite device according to claim 1, characterized in that The material of the perovskite layer has an ABX3 structure; wherein A includes at least one of methylamine, formamidine, and cesium; B includes at least one of Pb and Sn; and X includes at least one of I, Br, Cl, IBr, and ICl.
5. The perovskite device according to claim 1, characterized in that The electron transport layer comprises a first electron transport layer and a second electron transport layer connected to each other; And / or, the material of the first electron transport layer includes C 60 、PC 61 BM, PC 71 At least one of BM; And / or, the material of the second electron transport layer includes at least one of BCP, SnO2, ZnO, and TiO2; And / or, the thickness of the first electron transport layer is 10 to 100 nm; And / or, the thickness of the second electron transport layer is 2 to 100 nm.
6. The perovskite device according to claim 5, characterized in that The perovskite device further comprises a conductive substrate, wherein the conductive substrate is located inside the perovskite device; And / or, the perovskite device also includes a hole transport layer, the material of which includes at least one of PTAA, Spiro-OMeTAD and its derivatives, PACz and its derivatives, TAPC, NiO, and MPA-CPA; and / or, the perovskite device also includes a metal electrode layer, the material of which includes at least one of Cu, Ag, Al, Cr, and Au.
7. The perovskite device according to claim 6, characterized in that: The thickness of the hole transport layer is 1 to 200 nm; And / or, the thickness of the metal electrode layer is 80-200 nm.
8. The perovskite device according to claim 6, characterized in that: The perovskite device is a formal structure or a trans structure; wherein the formal structure includes a conductive substrate, a second electron transport layer, a first electron transport layer, an electron buffer layer, a perovskite layer, a hole transport layer, a metal electrode layer and an encapsulation layer stacked in sequence from bottom to top; the trans structure includes a conductive substrate, a hole transport layer, a perovskite layer, an electron buffer layer, a first electron transport layer, a second electron transport layer, a metal electrode layer and an encapsulation layer stacked in sequence from bottom to top.
9. The method for preparing a perovskite device according to claim 8, characterized in that: The following steps are involved: The electron buffer layer, the perovskite layer, the first electron transport layer, the second electron transport layer, the metal electrode layer and the hole transport layer are respectively deposited on the conductive substrate, and then the encapsulation layer is deposited on the outer surface to obtain the perovskite device.
10. Use of the perovskite device according to any one of claims 1 to 8 in a photovoltaic cell, a light emitting diode, a photodetector, a memristor or a laser.